Germany, pacifism and peace enforcement. - Dalgaard-Nielsen, Anja (Europe in change., 2006)
Germany, pacifism and peace enforcement is about the transformation of Germany?s security and defence policy in the time between the 1991 Gulf War and the 2003 war against Iraq. The book traces and explains the reaction of Europe?s biggest and potentially most powerful country to the ethnic wars of the 1990s, the emergence of large-scale terrorism, and the new US emphasis on pre-emptive strikes. Based on an analysis of Germany?s strategic culture it portrays Germany as a security actor and indicates the conditions and limits of the new German willingness to participate in international militar.